Endogenous cannabinoids mediate long-term synaptic depression in the nucleus accumbens - Robbe, David (The National Academy of Sciences, 2002)
Do endocannabinoids (eCBs) participate in long-term synaptic plasticity in the brain? Using pharmacological approaches and genetically altered mice, we show that stimulation of prelimbic cortex afferents at naturally occurring frequencies causes a long-term depression of nucleus accumbens glutamatergic synapses mediated by eCB release and presynaptic CB1 receptors. Translation of glutamate synaptic transmission into eCB retrograde signaling involved metabotropic glutamate receptors and postsynaptic intracellular Ca(2+) stores. These findings unveil the role of the eCB system in activity-dependent long-term synaptic plasticity and identify a mechanism by which marijuana can alter synaptic functions in the endogenous brain reward system.